AUTOMATIC ELECTROPLATING CHROME DAN DIGITALISASI PEMASARAN : INOVASI TEKNOLOGI PENINGKATAN SENTRA INDUSTRI PANDE BESI - Kristanti, Bella Arum; Wakidah, Riska Nur; Muktiningrum, Trinil (Jurnal Abdi Masyarakat, 2024)
Economic development is essential for enhancing community welfare, particularly in Kiping Village, Tulungagung Regency, East Java, where the majority of residents rely on blacksmithing. This traditional industry primarily produces agricultural tools like knives, sickles, and machetes using simple and conventional methods. However, the quality of these products often falls short in a competitive market increasingly dominated by manufactured alternatives. To revitalize the Blacksmith Small and Medium Industry (IKM) in Kiping, it is crucial to adopt a Smart Economy strategy that emphasizes entrepreneurship and innovation. Implementing modern techniques, such as automatic electroplating chrome technology, can significantly improve product quality, durability, and aesthetic appeal. This enhancement will not only help local blacksmiths compete with mass-produced items but also increase the perceived value of their products. Moreover, the current marketing practices, which rely heavily on collectors, limit the artisans' reach and profit margins. By integrating digital marketing strategies, blacksmiths can directly connect with consumers, expanding their market and securing better prices for their goods. This shift towards a more sustainable and resilient business model will empower local craftsmen, ensuring that they receive fair compensation for their work. Ultimately, fostering innovation and improving marketing strategies will not only enhance the competitiveness of Kiping’s blacksmiths but also contribute to the broader goal of local economic development, uplifting the community and securing a sustainable livelihood for its residents.